British and Irish diasporas : Societies, cultures and ideologies - Clark, J. C. D.; Bueltmann, Tanja; MacRaild, Donald M. (Book collections on Project MUSE., 2019)
This book offers the first integrated study of the formation of diasporas from the islands of Ireland and Britain, and explores how the examples and experiences of the constituent nations and peoples of those islands compare.